Weight Reduction in Obese Adolescents with and without Binge Eating - Bishop-Gilyard, Chanelle T. (2010)
Little is known about binge eating (BE) in adolescents. The primary aim of the present study was to examine the relationship between BE and weight loss in adolescents (BMI ≥ 95(th) percentile) enrolled in a randomized controlled trial of behavioral and pharmacologic treatment of obesity. Participants were 82 treatment-seeking adolescents (BMI = 37.9 ± 3.8 kg/m(2); age = 14.1 ± 1.2 years; 67% females; 42% African American, 55% Caucasian). Participants completed the Children’s Depression Inventory, the Piers Harris Self-Esteem Questionnaire, and the Eating Inventory (including cognitive restraint, disinhibition, and hunger scales). BE was assessed by a questionnaire and a confirmatory interview. At baseline, 24% of participants met criteria for BE (N=13 met full BED criteria; N = 7 met sub-threshold BE). There were no significant differences in percentage reduction in initial BMI between participants with or without BE at Month 6 (−7.0 ± 1.6% vs. −6.9 ± 0.9%) or Month 12 (−8.8 ± 2.4% vs. −8.3 ± 1.3%) (omnibus main effect BE p = 0.89, interaction BE*Time p = 0.84, interaction BE*Drug p = 0.61). The rate of BE declined significantly over time from 24% (n=20) at baseline to 8% (n=6) at month 6 and 3% (n=2) at month 12 (p=0.003). There were significant decreases in hunger and disinhibition as well as an increase in cognitive restraint over time (all p ≤ 0.0001). Findings suggest a combination of behavioral and pharmacologic therapy may produce both weight loss and improvement in binge eating.